Fine-Scale Effects of Boat Moorings on Soft Sediment Communities Masked in Large-Scale Comparisons - Macolino, Assunta C.; Dafforn, Katherine A.; Hedge, Luke H.; Poore, Alistair G. B.; Johnston, Emma L. (Frontiers in Marine Science, 2019)
Population growth is driving demand for recreational marine infrastructure, resulting in extensive coastal habitat modification. Boat moorings, for example, are popular for vessel storage and are known to be damaging to seagrass communities, yet little is known about how they influence unvegetated sediment habitats. Here we investigate effects of boat moorings on sediment infauna using metrics of community composition, diversity, total abundance and abundances of individual functional groups and dominant taxa. Metrics were compared at fine and larger spatial scales to investigate how spatial variability affects the ecological assessments in soft-sedimentary environments. Fine-scale models revealed changes in community composition and mollusc abundance with distance from moorings while sediment grain size was also an important predictor for composition, bivalve and polychaete abundances although the direction of effects varied. When the same metrics were compared at larger scales (i.e. boating infrastructure present or lacking) we found that spatial variability among locations was detected, but no effect of moorings. With increasing urbanisation and industrialisation of coastal areas there is a clear need to account for the scale of potential ecological effects in investigations of coastal infrastructure developments.